Simultaneous Kidney and Parathyroid Transplantation in the Management of Genetic Hypoparathyroidism in a Child. Issue 4 (16th March 2022) - Vallant, Natalie; Sinha, Manish D.; Cheung, Moira; Ware, Nick; Jones, Helen; Buck, Jackie; Boffa, Catherine; Irving, Melita; Carroll, Paul V.; Hubbard, Johnathan; Gökmen, Refik; Rees, Lesley; et al.
Abstract : Background: Genetically determined hypoparathyroidism can lead to life-threatening episodes of hypocalcemia and, more rarely, to end-stage kidney disease at a young age. Parathyroid allotransplantation is the only curative treatment, and in patients already receiving immunosuppression for kidney transplantation, there may be little additional risk involved. We report the first such case in a child. Methods: An 11-y-old girl, known to have hypoparathyroidism secondary to an activating pathogenic variant in the calcium-sensing receptor, developed end-stage kidney disease and was started on intermittent hemodialysis. Since the age of 2.5 y, she had been receiving treatment with exogenous synthetic parathyroid hormone (PTH). In June 2019, at the age of 11.8 y, she received a living-donor kidney and simultaneous parathyroid gland transplant from her father. The kidney was implanted into the right iliac fossa, followed by implantation of the parathyroid gland into the exposed rectus muscle. Results: The kidney graft showed immediate function while the intrinsic serum PTH level remained low at 3 ng/L. Exogenous PTH infusion was reduced on day 6 posttransplantation to stimulate PTH production by the new gland, which resulted in improving intrinsic PTH concentrations of 28 ng/L by day 9. Twelve months after transplantation, PTH levels remain in normal range and the kidney graft function is stable with a serum creatinine of 110 μmol/L. Conclusions: Simultaneous living donation and transplantation of a kidney and a parathyroid gland into a child is safe and feasible and has the potential to cure primary hypoparathyroidism as well as kidney failure.